Labor Productivity In Emerging Markets: Evidence From Brazil, China, India, And Russia (BRIC) - Kang, Young-Hee; Na, Kyunga; Kim, Yang Sok (Journal of Applied Business Research, 2018)
Despite the great amount of attention to emerging markets, much still remains unknown about firm performance in emerging economies. To fill this gap, this study aims to investigate factors that influence labor productivity of firms in Brazil, China, India, and Russia (BRIC countries). This study focuses on features of business environments of emerging markets such as informality, corruption, foreign ownership, and external audit. Using a cross-national sample of 8,885 firms from the World Bank Enterprise Surveys dataset, we find that informality is negatively associated with labor productivity, while corruption and external audit are positively related to labor productivity. Implications will be discussed.
Keywords: Labor Productivity; BRIC countries; Informality; Bribery; External Audit